2021
DOI: 10.1155/2021/6641838
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Molecular Mechanism of Erxian Decoction in Treating Osteoporosis Based on Formula Optimization Model

Abstract: Osteoporosis (OP) is a highly prevalent orthopedic condition in postmenopausal women and the elderly. Currently, OP treatments mainly include bisphosphonates, receptor activator of nuclear factor kappa-B ligand (RANKL) antibody therapy, selective estrogen receptor modulators, teriparatide (PTH1-34), and menopausal hormone therapy. However, increasing evidence has indicated these treatments may exert serious side effects. In recent years, Traditional Chinese Medicine (TCM) has become popular for treating orthop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 103 publications
(125 reference statements)
0
28
0
Order By: Relevance
“…Whether botanical drugs or ingredients in the formula are necessary, especially when treating a specific disease, still needs analysis and verification. Through compound optimization, these botanical drugs and components with a better intervention effect can be screened out, while those botanical drugs and components with the antagonistic effect and even side effects are removed, making the compound simpler and more effective ( Wang et al, 2020a ; Wang et al, 2020b ; Gao et al, 2020 ; Yang et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Whether botanical drugs or ingredients in the formula are necessary, especially when treating a specific disease, still needs analysis and verification. Through compound optimization, these botanical drugs and components with a better intervention effect can be screened out, while those botanical drugs and components with the antagonistic effect and even side effects are removed, making the compound simpler and more effective ( Wang et al, 2020a ; Wang et al, 2020b ; Gao et al, 2020 ; Yang et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…The level of TNF-α was reported to be increased significantly in LPS-stimulated BMDMs (Liu et al, 2020). Comparatively, TNF-α could be reduced by baicalin (MOL002776) in the blood of sepsis mice (Chen et al, 2016) A Chinese formula, RDN, had been proved to ameliorate LPSinduced acute lung injury by downregulating TNF-α (Yang et al, 2021). 3) IL-1β: This is also a typical pro-inflammatory factor, which could promote T cells to further produce a large number of inflammatory mediators, which could reduce the body's immune function and destroy the barrier function of various tissues and organs, leading to the spread of systemic inflammatory response (Kamisoglu et al, 2015).…”
Section: Kegg Enrichment Analysis Of Critical Functional Ingredients Group Targetsmentioning
confidence: 99%
“…3) IL-1β: This is also a typical pro-inflammatory factor, which could promote T cells to further produce a large number of inflammatory mediators, which could reduce the body's immune function and destroy the barrier function of various tissues and organs, leading to the spread of systemic inflammatory response (Kamisoglu et al, 2015). Comparatively, it was proved to be downregulated by RDN and to ameliorate LPS-induced acute lung injury (Yang et al, 2021). It was indicated to be decreased by CX (Lv et al, 2012) and reported to be reduced by baicalin (MOL002776) in the sera of bacterial infected mice, significantly, thereby improving mouse survival in bacterial sepsis , and to have been reduced by caffeic acid [MOL000223 (CX, DS, and HH)] in LPS-stimulated macrophages (Chen et al, 2019).…”
Section: Kegg Enrichment Analysis Of Critical Functional Ingredients Group Targetsmentioning
confidence: 99%
See 2 more Smart Citations